Ta có: [TEX]\Delta BEH \sim \Delta BCD \Rightarrow \dfrac{{BH}}{{BD}} = \dfrac{{BE}}{{BC}} \Rightarrow BH.BC = BE.BD\left( 1 \right)[/TEX]
Lại có: [TEX]\Delta BHA \sim \Delta BAC \Rightarrow \dfrac{{BH}}{{BA}} = \dfrac{{BA}}{{BC}} \Rightarrow BH.BC = B{A^2}[/TEX]
Mà: [TEX]BA = BF \Rightarrow BC.BH = B{A^2} = B{F^2}\left( 2 \right)[/TEX]
Từ [TEX](1)[/TEX] và [TEX](2)[/TEX] suy ra [TEX]BE.BD = B{F^2} \Rightarrow \dfrac{{BF}}{{BE}} = \dfrac{{BD}}{{BF}}[/TEX]
Xét [TEX]\Delta BEF[/TEX] và [TEX]\Delta BFD[/TEX] có:
[TEX]\widehat B:chung\\
\dfrac{{BF}}{{BE}} = \dfrac{{BD}}{{BF}}\left( {cmt} \right)\\
\Rightarrow \Delta BEF \sim \Delta BFD\\
\Rightarrow \widehat {BFE} = \widehat {BDF}\left( {đpcm} \right)[/TEX]